Direct medical costs of severe hypoglycaemic events in patients with type 2 diabetes in England: A retrospective database study. Issue 6 (23rd May 2017) - Holbrook, Tim; Tang, Yuexin; Das, Romita; Shankar, R. Ravi; Tunceli, Kaan; Williams, Jean; Radican, Larry; Holden, Sarah E.; Morgan, Chris Ll.; Piercy, James; Currie, Craig J.
Summary: Aims: Hypoglycaemia in patients with diabetes can be induced by insulins and sulfonylureas. We assessed the real‐world impact of specific monotherapy and combination regimens on hypoglycaemic events requiring hospitalisation and related secondary costs to the English healthcare system. Methods: This retrospective observational study used the Clinical Practice Research Datalink with linked hospital admission data during 2008‐2012. Patients with type 2 diabetes mellitus (T2DM) using antihyperglycaemic agents (AHAs) were assigned to mutually exclusive subgroups (insulin‐ and non‐insulin‐containing regimens; treatment groups of interest; age group) based on treatment at index date (date of first AHA prescription). Outcomes were number and cost of hospital admissions with hypoglycaemic event‐related diagnosis codes. Results: We identified 110 206 patients with T2DM (mean age 64.9 years, time since diagnosis 5.4 years, HbA1c at index 7.4%), with 439 hypoglycaemic events requiring inpatient hospitalisation (mean length of stay 6.3 days, mean cost/stay £1351). Event rates and cost of stay were highest in patients treated with sulfonylurea‐ or insulin‐based regimens. Event rates, duration and cost of stay were higher in older patients. Conclusion: Rates of severe hypoglycaemic events varied substantially between T2DM regimens. In this study of patients treated in clinical practice in England, sulfonylurea‐ and insulin‐based regimens were associated with the highest event rates and costs associated with hospitalisation for severe hypoglycaemic events; hospitalisation for severe hypoglycaemic events was not observed with dipeptidyl peptidase‐4 inhibitor monotherapy or with metformin.